Consider the sequence: 8, 11, 14, 17, 20, 23, 26, The recursive definition is
![a_(n)=3+a_(n-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/9coxed69vs121i4ftk3fy3g83ori4v66v5.png)
Solution:
The given sequence is :- 8, 11, 14, 17, 20, 23, 26, .....
![\text { The first term is } a_(1)=8](https://img.qammunity.org/2020/formulas/mathematics/high-school/qfphtfg9ntno7e2d1oo3793c4c8nwnr0de.png)
Second term is
and so on
On analyzing the above series we can say
Each time we want a new term, we add on 3 to previous term which is as follows:-
8 + 3 = 11
11 + 3 = 14
14 + 3 = 17
17 + 3 = 20
20 + 3 = 23
23 + 3 = 26
And so on
This recursive step of adding on 3 to the prior term is written in the following general form:
![a_(n)=3+a_(n-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/9coxed69vs121i4ftk3fy3g83ori4v66v5.png)
Let's check the above recursive definition by substituting n = 2 we should get 11
![a_2 = 3 + a_(2-1)\\\\a_2 = 3 + a_(1)\\\\a_2 = 3 + 8 = 11](https://img.qammunity.org/2020/formulas/mathematics/high-school/yqie5jh67r5ozgxerfad3422xknddvblrj.png)
Thus the required recursive definition is found